2019
DOI: 10.1101/832154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of electron transport is essential for photosystem I stability and plant growth

Abstract: AbstractLife depends on the ability of photosynthetic organisms to exploit sunlight to fix carbon dioxide into biomass. Photosynthesis is modulated by pathways such as cyclic and pseudocyclic electron flow (CEF and PCEF). CEF transfers electrons from photosystem I to the plastoquinone pool according to two mechanisms, one dependent on proton gradient regulators (PGR5/PGRL1) and the other on the type I NADH dehydrogenase (NDH) complex. PCEF uses electrons from photosystem I to r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Similar functional redundancy was observed between FDPs and NDH-1 as well as PGRL1/PGR5 in the moss P. patens (Storti, Puggioni, et al, 2020a;Storti, Segalla, et al, 2020b). In Synechocystis, absence of both Flv1/3 and NDH-1 1/2 was even lethal when cells were moved from conditions of high CO 2 concentration and low light to air-level CO 2 concentration and high light, as in addition to exacerbated impairment of PSI oxidation, these mutants were unable to induce accumulation of proteins related to the CCM (Nikkanen et al, 2020).…”
Section: Nadh Dehydrogenase-like Complexessupporting
confidence: 69%
“…Similar functional redundancy was observed between FDPs and NDH-1 as well as PGRL1/PGR5 in the moss P. patens (Storti, Puggioni, et al, 2020a;Storti, Segalla, et al, 2020b). In Synechocystis, absence of both Flv1/3 and NDH-1 1/2 was even lethal when cells were moved from conditions of high CO 2 concentration and low light to air-level CO 2 concentration and high light, as in addition to exacerbated impairment of PSI oxidation, these mutants were unable to induce accumulation of proteins related to the CCM (Nikkanen et al, 2020).…”
Section: Nadh Dehydrogenase-like Complexessupporting
confidence: 69%
“…In this study, we investigated the roles of FLV and photorespiration in regulating photosynthetic electron transport in the basal land plant M. polymorpha using the mutants deficient in FLV1 and PGR5. As shown in the preceding studies in M. polymorpha and P. patens ( Gerotto et al, 2016 ; Shimakawa et al, 2017 ; Storti et al, 2019 ; Storti et al, 2020 ), FLV is indispensable for keeping P700 oxidized in high light conditions unless the light exposure is prolonged for an acclimation ( Figure 5 ; Shimakawa et al, 2017 ). Meanwhile, Y(II) and qL decreased at 2kPa O 2 even in flv1 , indicating that there is another O 2 -dependent electron sink that should be photorespiration ( Hanawa et al, 2017 ).…”
Section: Discussionmentioning
confidence: 56%
“…In these land plants, photorespiration keeps photosynthetic linear electron flow at the CO 2 -compensation point ( Hanawa et al, 2017 ), whereas FLV functions for this in cyanobacteria ( Shimakawa et al, 2016 ; Santana-Sanchez et al, 2019 ). Recently, Storti and co-workers reported that in the moss Physcomitrium patens the lack of PGRL1 has little effect on photoprotection except when combined with a mutation in the gene for FLV, which results in photo-oxidative damage of PSI, especially under fluctuating light ( Storti et al, 2019 ; Storti et al, 2020 ). The PGR5- and PGRL1-dependent regulatory mechanism is therefore assumed to be dispensable for P700 oxidation in the presence of the electron sink mediated by FLV as in the cases that a heterologous expression of FLV complements P700 oxidation in the mutants of Arabidopsis thaliana and Oryza sativa deficient in PGR5 ( Yamamoto et al, 2016 ; Wada et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen consumption and evolution were evaluated as in Storti et al (2020) with a Clark-type O2 electrode (Hansatech, King's Lynn, UK). In brief, two protonema disks of about 1 cm of diameter coming from 10 days old plates were introduced in the measurement chamber filled with 2 mL of a solution containing NaCO3 0.1 mM maintained at 23°C.…”
Section: Oxygen Consumption and Oxygen Evolutionmentioning
confidence: 99%
“…ETR was calculated as the ECS signal in light (SL) subtracted from the SD and normalized to the sample PSI content. At the end of the fifth min, the light was switched off to follow relaxation kinetics and evaluate the proton motive force (pmf) generated during light treatment as in Storti et al, (2020). The pmf was determined as the difference of the maximum signal at the light steady-state and minimum level of ECS in the dark and normalized to total charge separation PSI.…”
Section: Spectroscopic Analysesmentioning
confidence: 99%